Consumer Perceptions and Preferences of Beverage Products in Malang City - Mohammad Saifur Rohman; Mifetika Lukitasari; Dwi Adi Nugroho; Nashi Widodo; Inggita Kusumastuty; Nur Ida Panca Nugrahini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to investigate the consumer perceptions and preferences of beverage products in Malang City, East Java. This study uses a Mixing theory approach, which analyzes research data quantitatively by using descriptive analysis, and qualitatively. The population is all consumers of beverage products in Malang city, where 220 consumers were selected as research samples through purposive random sampling. Primary data were collected using a questionnaire. Types of drinks that are commonly consumed by the local community include soft drinks, tea, milk, coffee, health drinks, and beverages included in "other" category. Furthermore, the most consumed beverage is coffee. The results demonstrate that the choice of beverage products is greater based on the health and refreshing benefits. In terms of purchasing methods, most consumers prefer buying directly at the nearest store. This finding is a strong signal for beverage producers to market the products widely to reach small stores in residential areas. Producers of beverages other than coffee are suggested to emphasize the refreshing or health benefits of the beverage products to gain consumers' preference.